THE EFFECT OF HIGHER NERVOUS ACTIVITY TYPE ON THE CONTENT OF PHOSPHORUS IN THE BLOOD OF COWS - Zhurenko, О. V.; Karpovskyi, V. І.; Danchuk, O. V.; Trokoz, V. O. (Scientific Progress & Innovations, 2019)
The processes of excitation and inhibition are the main functional characteristics of the nervous system activity. The purpose of the study was to determine the extent and nature of the nervous system typological features’ influence on the content of phosphorus in cow body. Blood samples from animals taken from the jugular vein in the morning before feeding served as the material for the research. Blood sampling was con-ducted twice a year, in summer and winter. The studies have shown that phosphorus content in different blood fractions of animals with different types of HNA did not go beyond physiological limits. The time of year had a reliable effect on phosphorus content in the whole blood and its serum only in cows of WN type. According to the research results of inorganic phosphorus content in the blood serum of cows with different types of HNA, the content of inorganic phosphorus in serum did not go beyond physiological limits and made 4.2–5.1 mg/100 ml. It was established that the intensity of nervous processes in the summer is reliably relat-ed to phosphorus content in the whole blood (r=0.68; p<0.01), serum (r=0.66; p<0.01) and blood cells (r=0.56; p<0.05). As to the winter, these relationships weaken. The coefficient of determination of the strength of nerve processes with phosphorus content indicates that in the summer of 31 to 47 % (p<0.05–0.01) of the content of this element in different blood fractions due to the variability of indicators of the strength of nerve processes. The mobility of nervous processes, regardless of the time of year, was reliably unrelated to the content of inorganic phosphorus in the blood serum of cows (r=0.08–0.34). According to the regression analysis the reliable dependence of phosphorus content in the whole blood of cows on the mobili-ty of nervous processes was not established. Nervous process equilibrium significantly influenced phospho-rus content in the blood of cows in winter − ղ²ᵪ=0.50 (p<0.01) and in blood cells depending on the time of the year within − ղ²ᵪ=0.36–0.40 (p<0.05 to 0.01). The determination coefficient of nervous processes inten-sity connected with phosphorus content indicates that in the summer from 31 to 47 % (p<0.05–0.01) of this element content in different blood fractions is stipulated by the variability of the intensity indicators of nerv-ous processes. The results of multi-factor variance analysis revealed the reliable dependence between the type of higher nervous activity and phosphorus content in the whole blood and blood cells of cows (F=3.98–6.62>FU=3.01; p<0.05–0.001). Unlike typological characteristics of the nervous system, the time of year does not have a significant effect on the content of phosphorus in blood cells (F=0.24<FU=4.26; p>0.05), but has a significant effect on the content of phosphorus in the whole blood (F=7.03>FU=4.26; p<0.05) and blood serum (F=11.6>FU=4.26; p<0.01). Analyzing phosphorus content in the blood of cows, a reliable interaction between typological features of the nervous system and the time of the year was not established (F=0.09–0.68<FU=3.01; p>0.05).